The Catholic imagination - Greeley, Andrew M., 1928-2013 (University of California Press, 2000)
Catholics live in an enchanted world: a world of statues and holy water, stained glass and votive candles, saints and religious medals, rosary beads and holy pictures. But these Catholic paraphernalia are merely hints of a deeper and more pervasive religi.